The effect of access cavity design on apical debris extrusion - Ezgi Doğanay Yıldız (Mashhad University of Medical Sciences, 2023)
Objective: This study aimed to evaluate the effect of access cavity design on the amount of apically extruded debris in maxillary molars.Methods: Twenty-eight extracted maxillary molars were selected for this study. Inclusion criteria were caries-free teeth with mature roots and similar mesiobuccal root dimensions. The samples were randomly assigned into two groups, as follows: conservative endodontic cavity (CEC) and traditional endodontic cavity (TEC). Mesiobuccal canals of the teeth were instrumented using Reciproc instruments. Preweighed plastic tubes were used for collecting the apically extruded debris. The weights of plastic tubes (pre- and post-instrumentation) were determined using an electronic balance. The data were analyzed with an independent sample t-test, and a P-value < 0.05 was considered statistically significant.Results: The weight of apically extruded debris was significantly lower in the TEC group than in the CEC group (P =0.003).Conclusions: The results of this in vitro study demonstrated that TEC preparation was superior to the CEC approach in terms of minimizing apical extrusion of debris.